Co-pyrolysis of Fish with Pruning Waste for Biochar Production as an Amendment for Composite Composting in the Biorefinery Scenario - Salman Nisar; Josué Gonzalez-Camejo; Anna Laura Eusebi; Francesco Fatone (Chemical Engineering Transactions, 2025)
Increasing global fish production demands sustainable waste management for the proper disposal of process leftovers. Fish waste stabilisation using pyrolysis has the potential to stabilise this putrescible waste, as well as production of biochar for sustainable agricultural applications. This study investigated the influence of residence times at a fixed temperature (400°C) on the yield and quality of biochar by co-pyrolysis of fish and pruning waste. Results showed a decreasing trend of biochar yield with a decrease in residence time for pruning waste (PW) tests, whereas fish waste (FW) and PW blend (30:70 w/w) resulted in a relatively stable trend. Biochar obtained at 30 minutes residence time accounted for 42.1%, with a higher carbon content of 62.8% and H/C of 0.69, indicating thermal conversion and stable biochar. Furthermore, biochar exhibits a low concentration of trace elements, complying with safety and quality regulations for biochar.